The Narration of the Sermon of the Messenger of Allah (peace and blessings of Allah be upon him) in the Farewell Hajj - Hamad, Hussein Abid (Journal of Tikrit University for Humanities, 2024)
The sources mentioned three sermons of the Messenger of Allaah, Mohammed (peace and blessings of Allaah be upon him) in the farewell hajj, the sermons of the day of Arafah, the sermons of the day of sacrifice, and the sermons in the middle of the day of the Levant, and when we examine the texts of the narrations of the three sermons, we find that the sermon of the day of sacrifice contains a repetition of some of the sermon of the day of Arafah and more compatibility between the narration of the sermon of the day of Arafah and the narration of the sermon in the middle of the days of Tashreeq. The last sermon by the prophet is worthy of research and study because of its importance in explaining many concepts, and between the roundness of time and the number of months of the year and the determination of the haram months of them, the roundness of time means that he returned and matched his correct calculation when Allah created the heavens and the earth and ordered Muslims to adjust his account because the Arabic months correspond to the time Allah created and the acts of worship are in their true time. In these sermons, the prophet emphasized the inviolability of blood and money. Also, he advised the Muslimswith too many things like being mercy with women and to leave usury.